Imaging studies of the hindlimbs of pacas (Cuniculus paca) bred in captivity - Araujo, F. A. P. [UNESP]; Rahal, Sheila Canevese [UNESP]; Doiche, D. P. [UNESP]; Machado, M. R. F. [UNESP]; Vulcano, Luiz Carlos [UNESP]; Teixeira, Carlos Roberto [UNESP]; El-Warrak, A. O. (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2010)
Objective: To evaluate the hindlimbs of pacas bred in captivity using radiographic and computed tomography (CT) studies.Animals: Nine mature pacas (Cuniculus paca) 5.9-8.2 kg in body weight.Methods: Radiographical aspects of the bones of the hindlimbs were evaluated, and the Norberg angle and inclination angle were measured for each hindlimb. Anteversion angle were measured in CT examination.Results:The bone anatomy of the hindlimb of the paca was similar to that of the guinea pig, apart from two lunulae and a single fabella (lateral) which were observed. The Norberg angle had mean value of 130.56 degrees +/- 3.81 without any significant difference between testers. Inclination angles ranged from 142.44 degrees +/- 4.82 to 145.44 degrees +/- 4.09 by Hauptman's method, and from 144.94 degrees +/- 3.13 to 148.22 degrees +/- 3.25 by Montavon's method, for right and left hindlimbs respectively. Average values for the anteversion angles measured with CT ranged from 28.56 degrees +/- 5.56 to 32.91 degrees +/- 2.62.Clinical significance: The data may be used in future studies comparing the paca to other rodent species. In addition, the paca could be used as an animal model in orthopaedic research.
Keywords: Joint angles; rodents; orthopaedics; Computed tomography; pelvic limb